2019
DOI: 10.5296/jpag.v9i1.14439
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Organizational Transformation, Compensation and Organizational Culture on Performance of Regional Government Bureaucracy in Sumedang Regency West Java Province

Abstract: The purpose of this study was to analyze the influence the organizational transformation, compensation and organizational culture on the performance of local government bureaucracies in Sumedang Regency, West Java Province, Indonesia. This study used quantitative designs. The data collection was carried out by a survey to collect information from respondents using a questionnaire. The population in this study was all civil servants in Sumedang Regency, with a number of respondents amounting to 386 people based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Management Information System of an e-Proposal using ten indicators produces overall indicators with an r-count, which has a loading factor of more than 0. (Abubakar H. , 2016) and also the findings that prove that Organizational Transformation has a significant influence (Martini, Suradinata, Kusworo, Lambelanova, & Thahir, 2019). HR Capabilities has impact on Organizational Performance in the Distribution of Government Assistance with a coefficient of 0.237 and a t-value of 3.503 (more than 1.96, which means H2 is accepted).…”
Section: Respondent Demographicmentioning
confidence: 87%
See 1 more Smart Citation
“…Management Information System of an e-Proposal using ten indicators produces overall indicators with an r-count, which has a loading factor of more than 0. (Abubakar H. , 2016) and also the findings that prove that Organizational Transformation has a significant influence (Martini, Suradinata, Kusworo, Lambelanova, & Thahir, 2019). HR Capabilities has impact on Organizational Performance in the Distribution of Government Assistance with a coefficient of 0.237 and a t-value of 3.503 (more than 1.96, which means H2 is accepted).…”
Section: Respondent Demographicmentioning
confidence: 87%
“…Chart 4, Research Model (adjusted by Author's) Abubakar (2016), in his research, found that organizational transformation in the form of business process reengineering has a positive effect on organizational performance; this illustrates that business process reengineering aims at cost efficiency, improving customer service, improving quality, and increasing speed which can drive organizational performance improvement. Organizational transformation has a significant effect on the performance of the government bureaucracy (Martini, Suradinata, Kusworo, Lambelanova, & Thahir, 2019). Organizational change is the restructuring of resources and capabilities to improve organizational performance to create value and increase profits for stakeholders.…”
Section: Chart 3 Banper's E-proposal Mechanismmentioning
confidence: 99%
“…In line with Azimi (2021), governance is a scientific discipline that examines the relationship between citizens and the highest governing entity in the country (government) within the framework of authority and provision of public services. Suradinata, Kusworo, Lambelanova, and Thahir (2019) believes that governance can be categorized as a science and an art. As a science, governance is knowledge that studies the process of activity of public institutions in their function to realize state goals, universally applicable.…”
Section: Government Sciencementioning
confidence: 99%